Are Discovery Learning and Independent Learning Effective in Improving Students’ Cognitive Skills? - Novantri, Wira; Maison, Maison; Muslim, Muslim; Aftriyati, Lusi W (Indonesian Journal of Science and Mathematics Education, 2020)
Based on the theory, the success of students in learning is determined by learning model applied by the teacher and students’ independent learning skills. This research is a quasi experimental research with pretest and posttest design. The population of this research was students of class XI SMA N 3 Tebo in 2019/2020 academic year. The sampling technique used cluster random sampling. The research instruments used mathematical cognitive tests and student independent learning questionnaires. The data analysis technique used is two-way variance analysis with 3 × 3 factorial design. Based on the results of this researh, we can concluded that (1) There is a difference in the average of students’ mathematics cognitive skills based on the applied learning model, (2) There are differences in the average of students mathematics cognitive learning outcomes based on the level of independent learning, (3) there is no interaction between Discovery learning model and independent learning towards students’ mathematics cognitive skills.